The commercial mediator's handbook - Chern, Cyril (Milton Park, Abingdon, Oxon : Informa Law from Routledge, 2015)
'Mediation as a method of dispute resolution is well known and practised worldwide, and this book provides the knowledge necessary for those actively involved in mediation work as well as for those who need to learn the process. This is an invaluable guide on how to mediate, what forms should be used and what techniques can be applied by the mediator to obtain a successful result. It also provides essential guidance on how to deal with large, complex international commercial disputes and their effective administration. Key features of this book include: In-depth discussion of both the existing and historical international case law on mediation including its history under the British Common law, European Civil law and Muslim Shari'ah law. Analysis of the differences between the various forms of mediation agreements with sample wording to add to or modify these forms as needed. In-depth discussion of the ethical requirements relating to mediation and mediators. Sample forms for use in commencing mediation. In-depth discussion of actual mediations, how they should be conducted, techniques to use and sample forms. General forms for use in complex international mediation, form agenda and mediation statements. Mediator disclosure forms, questionnaires for potential mediators and parties and comparison of mediation agreements and sample forms. Discussion of how to effectively use witnesses and the preparation and presentation of witness statements in mediation. International case studies with statements of claims and responses.This book will be essential reading for those involved in international commercial and construction mediation'--
The Dispute Process: Why Settle? -- Why Mediate: It Is an Old Story -- Why Mediate Today -- The Development of Contemporary Mediation Worldwide -- The Process -- Interests and Negotiation -- Conducting a Mediation Session -- Preventing Settlement Remorse in Mediation -- Mediation Party Forms, Questionnaire, and Documents -- The Mediator's Pre-Mediation Information and Dispute Management -- Structured Mediation Boards : Forms and Documents -- What Does the Mediator Do -- Mediator Control and Payment -- Mediation Commencement and Other Issues -- Finding the Truth -- Mediation Styles -- Commercial Mediation Techniques -- Procedures, Proceedings and Check Lists -- Reaching Agreement -- Mediator Ethics -- Special Forms and Agreements -- Legal Issues in Mediation -- Additional Mediation Forms and Agreements -- Representing Parties In Mediation -- Advanced Techniques.
Includes bibliographical references and index.
Keywords: Mediation; Dispute resolution (Law); Business enterprises -- Law and legislation